Political Uncertainty and Cross-Border Acquisitions. (20th December 2017) - Cao, Chunfang; Li, Xiaoyang; Liu, Guilin
Abstract: Using national elections as sources of exogenous variation in uncertainty, we show that political uncertainty affects the volume and outcome of cross-border acquisitions. When a country is about to hold a national election, this deters foreign firms' inbound acquisitions, especially when the host country poses greater expropriation risk. An upcoming home country election encourages firms to conduct outbound cross-border acquisitions, especially to target countries with free-trade agreements, military allies, or countries with better governance. At transaction level, we show that announcement returns to cross-border deals incorporate political uncertainty considerations. Overall, these results shed light on the effects of political uncertainty through the cross-border acquisition channel.